Forest Landscape Restoration: increasing the positive impacts of forest restoration or simply the area under tree cover? - Mansourian, Stephanie; Stanturf, John A.; Derkyi, Mercy Afua Adutwumwaa; Engel, Vera Lex [UNESP] (Wiley, 2017)
Restoring forest landscapes is critical in the face of continued global forest loss and degradation. In this article, we explore some challenges underlying the delivery of global commitments to restore forest landscapes. We propose that three fundamental questions need to be resolved upfront for the effective implementation of Forest Landscape Restoration and related commitments: (1) What social and ecological landscape objectives are being sought through Forest Landscape Restoration? (2) How are specific areas being selected for restoration? (3) How is success measured when restoring forest landscapes? We believe that there is an urgent need to adequately answer these questions to successfully implement political commitments for large-scale forest restoration.
Keywords: Bonn Challenge; hectare targets; restoration scale